The Impact of Political Dynasty Practices on Indonesian Local Democracy - Dafrin Muksin; Ahmad Rizali Pawane; Sahrail Robo (Journal of Government and Politics (JGOP), 2024)
The negative impact of the practice of political dynasties is that power is concentrated in dynastic families where family members occupy strategic positions of power in the administration of politics and government, the strengthening of KKN practices, low levels of supervision, and closed spaces for competition in government. Gaining power in local democracy. This research will explore the impact of political dynasties on local Indonesian democracy. Qualitative methods were used as an approach in this research. This research uses secondary data in the form of documents, journals and other supporting data. After the data is collected, the data is managed using Nvivo 12 Plus. Next, a strict selection is carried out, analyzed, arranged systematically, and conclusions are drawn. This research concludes that the practice of political dynasties has impacts including corruption, Collusion, and Nepotism with a percentage of 20%, where the practice of political dynasties opens up space for KKN practices thereby hampering regional progress. The loss of supervision is 5%, namely, that government administration is running without good supervision. Maximum both from supervisory institutions and the community, competition losses amount to 45% where the practice of political dynasties closes the space for community competition in occupying strategic positions at the local level, and political domination occurs at 30%, namely that the government is run by prioritizing the element of kinship or family involvement to complete and fill strategic positions in government.